CaM kinase II-δ is required for diabetic hyperglycemia and retinopathy but not nephropathy - Chen, Jessy; Fleming, Thomas; Katz, Sylvia; Dewenter, Matthias; Hofmann, Kai; Saadatmand, Ali R.; Kronlage, Mariya; Werner, Moritz P.; Pokrandt, Bianca; Schreiter, Friederike; Lin, Jihong; Katz, Daniel; et al. (Diabetes, 2021)
Type 2 diabetes has become a pandemic and leads to late diabetic complications of organs, including kidney and eye. Lowering hyperglycemia is the typical therapeutic goal in clinical medicine. However, hyperglycemia may only be a symptom of diabetes but not the sole cause of late diabetic complications; instead, other diabetes-related alterations could be causative. Here, we studied the role of CaM kinase II-δ (CaMKIIδ), which is known to be activated through diabetic metabolism. CaMKIIδ is expressed ubiquitously and might therefore affect several different organ systems. We crossed diabetic leptin receptor-mutant mice to mice lacking CaMKIIδ globally. Remarkably, CaMKIIδ-deficient diabetic mice did not develop hyperglycemia. As potential underlying mechanisms, we provide evidence for improved insulin sensing with increased glucose transport into skeletal muscle and also reduced hepatic glucose production. Despite normoglycemia, CaMKIIδ-deficient diabetic mice developed the full picture of diabetic nephropathy, but diabetic retinopathy was prevented. We also unmasked a retina-specific gene expression signature that might contribute to CaMKII-dependent retinal diabetic complications. These data challenge the clinical concept of normalizing hyperglycemia in diabetes as a causative treatment strategy for late diabetic complications and call for a more detailed analysis of intracellular metabolic signals in different diabetic organs.